Chinnovation : how Chinese innovators are changing the world - Tan, Yinglan (Hoboken, N.J. : Wiley ; Chichester : John Wiley, 2011)
It is widely-believed that China's entrepreneur class has grown and their businesses are succeeding primarily due to their knowledge of the domestic market, quick adaptation market changes, and their resourcefulness. But innovation? Forget about it. Well, not quite. Drawing on a wealth of on-the-ground stories and thorough research, Chinnovation: How Chinese Innovators are Changing the World shows how Chinese companies of every stripe have dispelled this myth and overcome the barriers to successful, profitable innovation. China's rapid economic growth has made it a crucial market but multinational corporations are now competing with China's own homegrown businesses. Chinnovation: How Chinese Innovators are Changing the World uncovers the common threads amongst Chinese entrepreneurs as they reach into a wider world.
Includes bibliographical references and index.
Print version record.
Keywords: Since 2000; Entrepreneurship -- China; Technological innovations -- China; China -- Economic conditions -- 2000-; China -- Foreign economic relations; Business; BUSINESS & ECONOMICS -- Entrepreneurship; Economic history; Entrepreneurship; International economic relations; Technological innovations; China -- Economic conditions -- 2000-; China -- Foreign economic relations; China; Electronic books